2009
DOI: 10.1186/1756-9966-28-82
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulated miR-9 and miR-433 in human gastric carcinoma

Abstract: Background: MircoRNAs(miRNAs) are short, endogenously non-coding RNAs. The abnormal expression of miRNAs may be valuable for the diagnosis and treatment of tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
125
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(132 citation statements)
references
References 25 publications
6
125
0
1
Order By: Relevance
“…In addition to analysis of hsa-miR-9 methylation status, microRNA expression studies have shown that hsa-miR-9 expression is downregulated for several cancer sites, including breast (Lehmann et al, 2008;Hsu et al, 2009) Hsa-miR-9 methylation and renal cell carcinoma MAT Hildebrandt et al gastric (Luo et al, 2009) and ovarian (Laios et al, 2008). Furthermore, studies of liver (Budhu et al, 2008), breast (Iorio et al, 2005) and colorectal (Bandres et al, 2009) cancers have shown that altered hsa-miR-9 expression was associated with metastatic tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to analysis of hsa-miR-9 methylation status, microRNA expression studies have shown that hsa-miR-9 expression is downregulated for several cancer sites, including breast (Lehmann et al, 2008;Hsu et al, 2009) Hsa-miR-9 methylation and renal cell carcinoma MAT Hildebrandt et al gastric (Luo et al, 2009) and ovarian (Laios et al, 2008). Furthermore, studies of liver (Budhu et al, 2008), breast (Iorio et al, 2005) and colorectal (Bandres et al, 2009) cancers have shown that altered hsa-miR-9 expression was associated with metastatic tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings indicate that miR-9 plays a tumor-suppressive role via repressing tumor-associated genes (NFκB1 and RAB34) in gastric cancer. 29,33 Significantly, in human cancers, miR-9 expression levels or methylation status are associated with several clinicopathological features, such as tumor grade, metastatic status and survival rate. 23,27,31 Contrary to the above results, it has been showed that miR-9 is significantly deregulated in breast cancer or colorectal cancer, with increasing cancer migration, through repression of α-cadherin or E-cadherin expression.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30] Several lines of evidence have indicated that miR-9 can function as a tumor suppressor in various cancers. 23,24,27,29,[31][32][33] In gastric cancer, miR-9 is under-expressed and ectopic expression of miR-9 can influence cell growth and the cell cycle. 24,29,32,33 However, there is no study examining the mechanisms involved in the differential regulation of all three miR-9 gene loci.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a number of miRNAs that are associated with gastric cancer have been identified to date, the role of many of them in tumorigenesis and the underlying mechanism remain to be determined. Recently, we and others have identified some miRNAs deregulated in gastric cancer, such as downregulation of miR-141, miR-143, miR-145, miR-9 and miR-218 [11][12][13][14], and upregulation of miR-21, miR-150 and 106a [15][16][17][18]. Nevertheless, until very recently, the function and regulation of these miRNAs in gastric cancer have hardly been explored.…”
Section: Introductionmentioning
confidence: 99%